Penataan Ruang Terbuka Publik sebagai Wadah Aktivitas Warga pada Permukiman di Tepian Sungai Musi, Palembang - Maya Fitri Oktarini; Rahma D. Kesman; Aulyandini Amalia Zahra Putri; Maulisa Nuari; M. Raihan Fahreza; Albert Subari; Nur Azizah (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2022)
The planning riverside area can be a solution for the provision of public open space. The planning should promote the special character of the landscape and the community’s social culture. Open spaces in dense settlements use for expansion of the cramped house for daily activities and socializing between residents. The research location is in a settlement around the Ampera Bridge in Palembang. This study aims to present an alternative riverbank open space design based on the specific of the physical conditions and activities of riverside settlement. Observation includes the number of types of users, activities, area, and facilities. The results showed that active points were found in seven open spaces. The intensity and type of activity is influenced by the area, panorama, and facilities. Access to the river is the most important element in designing open spaces on the banks of the river. Residents' activities are often related to rivers. The access will revive the use of open space as a link between the river and the daily activities of residents. The arrangement also needs to be equipped with additional facilities of the daily needs for the resident’s reason to visit open spaces.